Cold housing in mild-climate countries: A study of indoor environmental quality and comfort preferences in homes, Adelaide, Australia. (15th March 2019) - Daniel, Lyrian; Baker, Emma; Williamson, Terence
Abstract: International evidence suggests that cold housing – and its effects on health – is not just confined to countries with very cold winters. Rather, a small but increasing body of work is revealing that unacceptably low indoor temperatures are often experienced in housing in mild-climate countries. This paper presents the findings from a field study of wintertime thermal comfort conditions in metropolitan Adelaide, Australia. Participants were selected from a large random sample of 4500 Australian households in the Australian Housing Conditions Dataset (AHCD). Nineteen households who self-identified in the dataset as unable to keep warm in their homes in cold weather were included in the study. Each household was interviewed to assess their heating practices and attitudes, invited to complete a daily comfort survey, and had the temperature and humidity in their homes recorded. On average, internal temperatures in the sample houses were well below recommended minimum temperature thresholds and respondents reported low satisfaction with their indoor thermal environment. The majority of households had no plans to make changes to their house to improve wintertime indoor conditions; rather, participants demonstrated a wide variety of warmth practices mainly directed toward achieving comfort conditions in close proximity to their body instead of throughout the entire room. The results from this small, exploratory study of wintertime housing conditions suggest that cold housing is a real and immediate problem for many households, despite Australia's relatively mild climates. Highlights: Cold housing is increasingly recognised as a problem for mild-climate countries. Internal temperatures in the sample houses were, on average, well below 18 °C. Households reported low satisfaction with their indoor thermal environment. Households coped by warming their person rather than their living spaces.